MODEL PEMBELAJARAN DEMONSTRASI UNTUK MENINGKATKAN KEAKTIFAN SISWA SEKOLAH MENENGAH KEJURUAN - Bagus Yulianta; Samidjo; Suparmin (JURNAL VOKASI DEWANTARA (JVD), 2025)
This study aims to analyze the increase in student activity by applying the demonstrationmethod and Classroom Action Research or PTK. This type of research is descriptiveresearch, namely a study that seeks to answer existing problems based on article data ornational and international journals which aims to find out: ( 1) Demonstration LearningModel Process to Increase the Activeness of Vocational High School Students. (2)Application of the Demonstration Learning Model to Increase the Activeness of VocationalHigh School Students The results of the research are based on the results of previousresearch or research that has been done, showing that the Demonstration Learning Modelis to increase the activity of Vocational High School students. The increase can be seen fromthe students' learning interest in carrying out practicum during the learning process ofVocational High School students. The type of research conducted was this research usingdescriptive quantitative methods Analysis of Demonstration Learning Methods to increasethe activeness of vocational high school students. Classroom Action Research is researchconducted with the aim of arousing enthusiasm and motivation and improving studentlearning outcomes in class. The study used was The study of the National Articles consistsof the title, background of the problem, formulation of the problem, research methods,research results and conclusions. While the study of the book includes the understandingand explanations of experts as well as relevant previous research results..